ANALYSIS RELATIONSHIP BETWEEN FINANCIAL MANAGEMENT EFFECTIVENESS AND CAPITAL STRUCTURE - Nunik Nurmalasari; Wiwin Maysaroh; Intan Maharrani; Rizki Fadilah; Jojo Jojo; Pupung Purnamasari (STIESA Press, 2024)
Financial management is very important, especially for a company to create a good capital structure so that it can finance all operational activities and achieve the company's goals effectively and efficiently. An optimal capital structure will help companies manage risks and maximize company value so that it can help investors in deciding on the right investment container, which is expected to generate profits. This research aims to analyze the relationship between the effectiveness of financial management and capital structure in food and beverage companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (BEI) for the 2022-2023 period. This research uses descriptive verification methods with purposive sampling techniques to select 24 food and beverage companies that published complete financial reports during that period. The variables studied include the effectiveness of financial management as measured by Return on Assets (ROA) and capital structure as measured by the Debt to Equity Ratio (DER). The research results show that there is a negative and significant relationship between the effectiveness of financial management and capital structure. In other words, the higher the effectiveness of financial management, the lower the use of debt in the company's capital structure. This research contributes to knowledge about how the effectiveness of financial management influences the capital structure of food and beverage companies in Indonesia